Genome-Wide Identification of Dickeya solani Transcriptional Units Up-Regulated in Response to Plant Tissues From a Crop-Host Solanum tuberosum and a Weed-Host Solanum dulcamara - Czajkowski, Robert; Fikowicz-Krosko, Jakub; Maciag, Tomasz; Rabalski, Lukasz; Czaplewska, Paulina; Jafra, Sylwia; Richert, Malwina; Krychowiak-Maśnicka, Marta; Hugouvieux-Cotte-Pattat, Nicole (Frontiers in Plant Science, 2020)
Dickeya solani is a Gram-negative bacterium able to cause disease symptoms on a variety of crop and ornamental plants worldwide. Weeds including Solanum dulcamara (bittersweet nightshade) growing near agricultural fields have been reported to support populations of soft rot bacteria in natural settings. However, little is known about the specific interaction of D. solani with such weed plants that may contribute to its success as an agricultural pathogen. The aim of this work was to assess the interaction of D. solani with its crop plant (Solanum tuberosum) and an alternative (S. dulcamara) host plant. From a collection of 10,000 Tn5 transposon mutants of D. solani IPO2222 carrying an inducible, promotorless gusA reporter gene, 210 were identified that exhibited plant tissue-dependent expression of the gene into which the Tn5 insertion had occurred. Thirteen Tn5 mutants exhibiting the greatest plant tissue induction of such genes in S. tuberosum or S. dulcamara as measured by qRT-PCR were assessed for plant host colonization, virulence, and ability to macerate plant tissue, as well as phenotypes likely to contribute to the ecological fitness of D. solani, including growth rate, carbon and nitrogen source utilization, motility, chemotaxis towards plant extracts, biofilm formation, growth under anaerobic conditions and quorum sensing. These 13 genes encode proteins involved in bacterial interactions with plants, with functions linked to cell envelope structure, chemotaxis and carbon metabolism. The selected 13 genes were differentially expressed in, and thus contributed preferentially to D. solani fitness in potato and/or S. dulcamara stem, leaf, and root tissues.